Valuing freedom of expression at the expense of linguistic aspect: The analysis of Kaur's selected poems - Lestari, Dewi Puspa; Alamsyah, Aam (Yayasan Mitra Persada Nusantara, 2024)
As a well-known poet, Rupi Kaur has written several poems which attract worldwide accolades. The present study explores several important aspects of her selected poems, such as feminism, humor, and irony. It was conducted qualitatively. In this case, the researchers acted to analyze and collected the data consecutively. The findings indicated that the concepts of feminism described in her poems tend to be more liberal and radical. The use of crude language to depict women as